Correlation and path coefficient analysis in some durum wheat varieties and their F1 hybrids using line x tester analysis. - Tawfiq, Sherwan I.; Abdulkhaleq, Dana A.; -Umin, Bestoon O. Hamma (Sulaimani Journal for Pure and Applied Sciences, 2017)
The current experiment was carried out at Qlyasan research station/Faculty of Agricultural Sciences/University of Sulaimani, using seven durum wheat varieties according to lines × testers’ analysis system producing twelve crosses. The parent’s varieties (Bakrajo1, Gerardo 574 and Cham 3) were used as lines while the parental varieties (Ovanto, Acsad 65, Apio and Crezo) were used as testers. The seven parental varieties and their twelve F1 crosses were planted in Completely Randomized Block Designs and replicated three times to calculate the simple correlation coefficient and path analysis. The results of this experiment showed that parent 1 exhibited the maximum values for the characters grain yield/plant, number of days to 50% anthesis, plant height and number of spikes/plant, while the cross Bakrajo 1 × Acsad 65 recorded the higher value due to grain yield/plant. The character grain yield/plant recorded highly significant and positive correlation with 1000-grain weight and significant positive correlation with plant height and number of spikes/plant. The maximum positive direct effect on grain yield/plant recorded by the character number of grain/spike reaching 0.567, while maximum positive indirect effect on grain yield/plant recorded by Spike length via number of grains/spike with 0.432, the results showed that number of grains/spike, spike length as well as number of grains/spike have major contribution in increasing the yield and it must be considered when selecting wheat varieties in breeding programs.
Keywords: Correlation Analysis Path Coefficient Analysis LineTester Durum wheat